1927 Fla. Laws 212, § 19, pt. 14 (Vol. 2) - (:unkn) unknown (My University, 1927)
Granted the city council the authority to prohibit and regulate the sale, or use, of toy pistols, air guns, and slungshots
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES